Classrooms Without Walls: The Dynamics of Virtual and Hybrid Learning - Khalik, Fihris; Faradina, Anggia (PT. Anagata Sembagi Education, 2025)
This study aims to explore the dynamics of wall-less learning, particularly in the context of virtual and hybrid learning during the post-COVID-19 pandemic period. Using a qualitative approach, this research examines how teachers and students adapt to digital learning technologies, the challenges related to infrastructure and access, and the impact of changes in social interaction within the hybrid learning model. Data were collected through in-depth interviews, participatory observations, and document studies conducted in several schools implementing such learning models. The results reveal that the success of virtual and hybrid learning largely depends on technological adaptability, supportive home learning environments, and the active involvement of parents. However, limitations in technological access and reduced social interaction remain significant challenges. This study recommends strengthening collaboration among stakeholders and developing digital infrastructure to support inclusive and quality education in the digital transformation era.